Estimasi hujan-debit menggunaan model Mock, GR2M, dan Tank di Kawasan Pagilaran sebagai Dasar Perencanaan PLTMH - Rian Mantasa Salve Prastica; Destiana Wahyu Pratiwi (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2021)
Pagilaran has water scarcity and electricity issues. Studies have been conducted and conclude new findings. Pagilaran has potential topography as a future small lake location and has water resources for new electricity energy resources. The paper concerns about discharge prediction in Pagilaran catchment. No studies could confirm the availability of outflow from water resources in Pagilaran. The primary data of taking debit samples in Pagilaran could not be done yet due to difficult access to arrive. This paper focuses on analyzing rainfall-runoff simulation using the Mock model, Tank model, and GR2M model to estimate the discharge. The methods show the same patterns of outflow every year. The results indicate these methods do not have enormous differentiation. Besides, the results deal with the earlier study about discharge prediction in Pagilaran. The papers conclude that the techniques could deal with the estimation of rainfall-runoff simulation with incomplete data. Primary data are still necessary to verify the methods.